IS IT POSSIBLE TO UNDERSTAND AND WORK THERAPEUTICALLY WITH PSYCHOPATHS? A CRITICAL REVIEW - Reading, Kathryn (2013)
Psychopaths have been renowned for their chameleon-like guise and predatory nature for centuries; however their characteristics still pose problems for society and psychiatry today. With the forthcoming edition of the Diagnostic and Statistical Manual (DSM-V), and the inclusion of an antisocial/ psychopathic personality disorder, the need to understand these individuals in terms of clinical, therapeutic and criminogenic needs has become increasingly relevant. This paper critically reviews the issues and questions concerning understanding and caring for psychopaths therapeutically. The review has been underpinned by a critical evaluation of the use of understanding vs explanation within psychiatry and human sciences, which has highlighted the specific need for empathic understanding within therapeutic relationships. Nursing has been established as a caring profession, composed of the basic need to understand patients in order to provide high quality and tailored care. It has however, been acknowledged that psychopathy may be a construct which professionals feel is ‘un-understandable’. This has resulted in themes of fear being identified, which may provoke stigma, particularly amongst staff seen to ‘care’ for this group of individuals. The discussion focuses on the ability of staff to care for those labelled ‘un-understandable’, and the whether the therapeutic relationship is capable of providing safety along with acceptance, genuineness and empathy to those labelled both ‘mad’ and ‘bad’. This has led to the question of whether explanations of psychopathy could suffice for staff caring for psychopaths. Another theme which has been highlighted in the literature is that of evil in relation to psychopathy. This led to arguments surrounding the appropriateness of this term in psychiatry. Finally, the review concludes with a discussion of limitations and implications of the review for future nursing practice and research.